Determinación de indicadores de cantidad y calidad del agua consumida en la ciudad de ventanas. - Morillo Estrada, Pablo David (2013)
Ventanas is a city in the coastal region of Ecuador in the province of Los Ríos. It has an urban population of about 40 000 inhabitants This investigation is a characterization method and socio-economic planning, created by authors. They have identified four economic strata in Ventanas. The largest economic capacity "A" is to up 4,10% of residential blocks in the city. The stratum B is to up 71,07%, 20,27% C has lower capacity and "D" isto up 4,56% of the 439 blocks surveyed. It Has been randomly selected to up 75 homes and it has been investigated for about 4 months. We analyzed monthly water consumption of each household selected, inflation in the region, the maximum temperature, precipitation, and maximum humidity of the city.